2021
DOI: 10.1186/s12889-021-11270-1
|View full text |Cite
|
Sign up to set email alerts
|

Stigmatization of Chinese and Asian-looking people during the COVID-19 pandemic in Germany

Abstract: Background The outbreak and global spread of COVID-19 was accompanied by an increase in reports of stigmatization of Chinese and Asian-looking people. The behavioral immune system provides a framework for stigmatization in response to infectious disease threats. Specifically, stigmatization might increase with rising levels of infectious disease threat. The present study aimed to examine this hypothesis during the early phase of the COVID-19 pandemic. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 40 publications
(47 reference statements)
1
3
0
2
Order By: Relevance
“…To our knowledge, this is one of the first studies providing extensive stigmatization patterns for COVID-19-related stigmatization in a German population at high risk of infection using latent class analysis. The relatively low rates of stigmatization in our study sample align with previous studies on COVID-19-related stigmatization in the German population [ 36 , 37 ]. In one study, stigmatizing attitudes towards people suffering from COVID-19 were investigated using two subscales „support for discrimination”and „blame”in 157 German participants in March 2020 [ 36 ].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…To our knowledge, this is one of the first studies providing extensive stigmatization patterns for COVID-19-related stigmatization in a German population at high risk of infection using latent class analysis. The relatively low rates of stigmatization in our study sample align with previous studies on COVID-19-related stigmatization in the German population [ 36 , 37 ]. In one study, stigmatizing attitudes towards people suffering from COVID-19 were investigated using two subscales „support for discrimination”and „blame”in 157 German participants in March 2020 [ 36 ].…”
Section: Discussionsupporting
confidence: 89%
“…The authors reported low to moderate amounts of stigmatization ( = 2.5 and = 1.4; scales range = 1–5) in the general population. Other authors investigated the hypothesis that stigmatization of Chinese and Asian-looking people increases in the general population of Germany with rising numbers of people infected with SARS-CoV-2 [ 37 ]. They found no evidence of an increase in the stigmatization of Chinese and Asian-looking people on interpersonal and societal levels.…”
Section: Discussionmentioning
confidence: 99%
“…Für Deutschland liegen aktuell nur wenige nicht-repräsentative Studien zu COVID-19-bezogener Stigmatisierung vor [ 13 15 ], die alle auf Fremdstigmatisierung ausgerichtet sind. In unserer Studie untersuchen wir hingegen die diesbezügliche „Selbststigmatisierung“, also die Stigmatisierung, die sich ein Individuum im Kontext von COVID-19 selbst auferlegt (siehe auch Ausführungen weiter unten).…”
Section: Introductionunclassified
“…Personal experience can range from infections within one's wider social network to infections in close social proximity (e.g., relatives; Kollmann et al, 2022 ;Weinstein, 1989 ). It may be especially influential as it provides more vivid and concrete information about the hazard ( Weinstein, 1989 ) and can trigger a set of disease-avoidance mechanisms known as the "Behavioral Immune System" (e.g., Koller et al, 2021 ;Schaller et al, 2021 ;Schaller and Park, 2011 ).…”
Section: Introductionmentioning
confidence: 99%